Jenis dan Langkah Penelitian Hadis - Nur, Sofyan (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2017)
Hadits, which is on the second hierarchy of Islamic law, always attracts the scholars to conduct the studies and discussions on it. Lacking of aspects in the study of hadits seems to open a vast space to discuss and study on the hadits. Through exploring the scholars’ works in the study of hadits, it is necessary to comprehend that the study of hadits has its own kinds and steps. These steps are the procedures that have to be passed through in the study in accordance with their own kinds. The objective of this study is to provide understanding and guidance in the study of hadits at once, in accordance with the kinds of study of the hadits which has to be passed through.